Anemoside B4 attenuates abdominal aortic aneurysm by limiting smooth muscle cell transdifferentiation and its mediated inflammation - Chu, Shuhan; Shan, Dan; He, Luling; Yang, Shilin; Feng, Yulin; Zhang, Yifeng; Yu, Jun (Frontiers in Immunology, 2024)
Abdominal aortic aneurysm (AAA) is a degenerative disease characterized by local abnormal dilation of the aorta accompanied by vascular smooth muscle cell (VSMC) dysfunction and chronic inflammation. VSMC dedifferentiation, transdifferentiation, and increased expression of matrix metalloproteinases (MMPs) are essential causes of AAA formation. Previous studies from us and others have shown that Anemoside B4 (AB4), a saponin from Pulsatilla chinensis, has anti-inflammatory, anti-tumor, and regulatory effects on VSMC dediferenciation. The current study aimed to investigate whether AB4 inhibits AAA development and its underlying mechanisms. By using an Ang II induced AAA model in vivo and cholesterol loading mediated VSMC to macrophage transdifferentiation model in vitro, our study demonstrated that AB4 could attenuate AAA pathogenesis, prevent VSMC dedifferentiation and transdifferentiation to macrophage-like cells, decrease vascular inflammation, and suppress MMP expression and activity. Furthermore, KLF4 overexpression attenuated the effects of AB4 on VSMC to macrophage-like cell transition and VSMC inflammation in vitro. In conclusion, AB4 protects against AAA formation in mice by inhibiting KLF4 mediated VSMC transdifferentiation and inflammation. Our study provides the first proof of concept of using AB4 for AAA management.